Peningkatan Mutu Pendidikan Melalui Kualitas Pendidik Di Tpq Al Iffah Kayuringin Bekasi - Riftyshafitri Riftyshafitri; EE. Junaedi Sastradiharja; Akhmad Shunhaji (Journal on Education, 2023)
This research uses a qualitative descriptive case study type approach. Data collection techniques using observation, interviews and documentation. Data analysis from the results of observations, interviews and documentation begins with data reduction, data presentation and ends with drawing conclusions. The results of this study contained five findings in this study, namely: 1) improving the quality of educators includes a number of first coverage matters, educator planning, second, coaching and development of educators. 2) The quality of education at TPQ Al Iffah, includes input, process and output quality of education, and an evaluation is carried out in every quality education activity to improve the quality of education at TPQ. 3) In terms of teaching, educators are still not good, because educators do not understand learning strategies and methods, so that the learning activities carried out are less attractive. 4) The process of recruiting educators at TPQ Al Iffah is still not well organized, namely there are several deficiencies such as no planning regarding the formation of an educator recruitment committee, no interview guidelines and no format for assessing the ability to read the Quran. 5) To improve the quality of education through the quality of educators at TPQ Al Iffah it is good because TPQ Al Iffah has provided learning workshops and how to teach the Qur'an with the yanbu'a method. Measurements carried out by TPQ include Educator indicators.